Relationship Between Walking Distance, Metabolic Equivalents and Handgrip Strength in Elderly - Nita Damayanti; Hartati Tuna; Ekawati Sutikno; Alita Dewi Percunda (Saniya Institute, 2025)
Physical function is crucial in the elderly, as physical endurance and muscle strength significantly impact the quality of life. Maintaining this function is essential to prevent disability, sarcopenia, frailty, and risk for metabolic disorders. This study aimed to explore the relationship between walking distance, METs, and hand grip strength (HGS) in the community-retirement elderly population. A total of 23 participants older adults from retirement community had measured body anthropometry, distance walking in 6 minutes, and hand grip strength. METS was calculated based on walking speed and body weight. Pearson correlation and linear regression were conducted to analyze the correlation. Hand grip strength was moderately correlated with walking distance (r=0,35) and weakly with METs (r=-0,18). Walking distance is negatively correlated with aged (r=-0.37) Regression indicated that age, weight, and HGS as walking distance performance variability. This was a preliminary study and finding that HGS as a predictor of mobility and functional endurance in elderly.